Predictive Value of a Medication Adherence Screening Tool on Hospital Readmission Rates in Patients with Congestive Heart Failure - Felix, Serena (The University of Arizona., 2013)
Class of 2013 Abstract === Specific Aims: To examine the relationship between hospital readmission rates and responses to a medication adherence questionnaire (Morisky) in patients with congestive heart failure (CHF). Methods: The Morisky questionnaire, assessing medication adherence, was administered to all CHF patients admitted from September 15, 2012 to March 7, 2013. Information collected from the electronic medical record (EMR) for all patients with complete Morisky questionnaires included: age, sex, ethnicity, insurance, height, weight, marital status, tobacco use, alcohol use, number of home medications, all-cause and CHF admission in the previous 365 days from when the questionnaire was administered as well as the following events/disease states: myocardial infarction, hypertension, atrial fibrillation, stroke, diabetes mellitus, peripheral vascular disease, chronic obstructive pulmonary disease, congestive heart disease and chronic kidney disease. Main Results: Of the 120 patients enrolled, 52% scored 1-5 on the Morisky questionnaire indicating some problem with medication adherence while 48% scored 0 (no problems). There was no correlation between the Morisky score and age (95% CI: -3.3-5.7), number of medications (95% CI: -0.26, 2.85), or number of comorbidities (95% CI: -1.02,0.03). The Morisky questionnaire was not predictive of all cause readmissions (95% CI: 0.35, 2.01) p = 0.691). For CHF readmissions the Morisky score was not significant (95% CI: 0.6, 4.11, p=0.358) but the confidence interval suggests a trend. Conclusion: There is no correlation between Morisky scores, age, comorbidities, and medication number. Readmission rates were not predicted by Morisky scores; with more participants a trend may be detected for CHF readmissions.